PENGEMBANGAN PERANGKAT AKUISISI DATA PORTABEL BERBASIS MIKROKONTROLER AT89C52 UNTUK PENYEIMBANGAN DI LAPANGAN - Zainal Abidin; Arief Indrabayu; Adi Santoso; Hariyadi Hariyadi (Mesin, 2002)
This paper describes the development of a portable microcontroller-based data acquisition system suitable for field balancing. The prototype was designed to have three channels. Channel 0 was designed to receive a DC signal and therefore suitable for reference signal, such as generated by optical sensor. In contrast, channels 1 and 2 were designed to receive AC signals and therefore suitable for vibration signals. In the design, the acquisition process was performed by three ADCs which sample data simultaneously, thus minimizing the phase difference between channels. The data obtained by ADC are then stored within memory, capable to store data as many as 8192 for each channel. The hardware is also equipped with a keypad modul as an input medium, an LCD modul as an output medium, and a rechargeable battery as a power supply. The software of this data acquitition system is classified into data-acquitition program and interface program. The performance of the prototype was tested using unbalance demontration setup and the results of measurement are compared to those obtained by MSA HP 35650 as a reference instrument. The measurement shows that results of measurement obtained by theprototype are relatively similar to those obtained by MSA.